Pengaruh Model Learning Cycle 5E (Engage, Explore, Explain, Elaboration, & Evaluate) Terhadap Kemampuan Berpikir Kritis Peserta Didik Kelas X MAN 1 Mataram - Baiq Rizkia Ayu Latifa; Ni Nyoman Sri Putu Verawati; Ahmad Harjono (Department of Physics Education, Universitas Mataram, 2017)
This study aims to determine the effect of learning cycle 5E model (Engage, Explore, Explain, Elaboration, & Evaluate) on studentÃ¢â¬â¢s critical thinking skills of class X in MAN 1 Mataram. This research type is quasi experiment with research design untreated control group with pretest and posttest design. The sample was selected by cluster random sampling technique and obtained X MIA 1 class as experiment class using learning cycle 5E model and X MIA 2 class as control class using cooperative learning type STAD model. The critical thinking abilityÃ¢â¬â¢s data collected by essay test that are 5 questions that have been tested for validation, reliability, difficulty level, and index of discrimination. Researchers used homogeneity test, normality test, t-test polled variance, and N-Gain test as statistical test. N-Gain test are used to determine the improvement of critical thinking skills in each indicator. The experimental class get improvement result in medium category for all indicators, while the control class get improvement in medium category on three indicators and two other indicators in low category. Based on result of hypothesis test can be concluded that there is effect of learning cycle 5E model to critical thinking ability of students.